Human Capital Development and Employee Performance in the Indonesian Telecommunications Sector - Willy Yusnandar; Irwan Syari Tanjung (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2026)
Despite extensive research examining the relationship between training, career development, and employee performance, empirical findings remain inconsistent, particularly in the telecommunications industry, where rapid technological change requires continuous human capital development. This study aims to analyze the effects of training and career development on employee performance at PT Telkomsel Medan Branch while providing empirical evidence from the perspective of Human Capital Theory. A quantitative approach was employed using a survey of 140 employees selected through the Slovin formula. Data were collected using structured questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that both training and career development have a positive and significant effect on employee performance, both partially and simultaneously (p < 0.05). Career development demonstrates a stronger contribution to employee performance than training, highlighting the importance of integrating competency development with long-term career opportunities. These findings reinforce Human Capital Theory by emphasizing that organizational investment in employee competencies and career development contributes to improved organizational performance. The study provides practical implications for designing integrated human resource development strategies in the telecommunications sector.